The Divinity of Christ in a Pluralistic World – A Study of Johannine Christology - Patrick Yankyera; John Kwabena Boachie; William Obeng-Denteh; Peter Adams (E-Journal of Religious and Theological Studies)
This paper explored the doctrine of the divinity of Christ within the context of a pluralistic world, where multiple religious traditions coexist, each claiming distinct revelations of divine truth. The Christian belief in the unique divinity of Jesus Christ has often been challenged by such pluralism, especially in the face of modern interreligious dialogues. This paper examined the historical, biblical, and theological foundations of Christ’s divinity, focusing on Johannine Christology as a primary source of high Christology. Additionally, it engaged contemporary debates on religious pluralism, exploring inclusivist, exclusivist, and pluralist approaches to Christ’s divine identity. The paper argued that while the divinity of Christ remains a central and non-negotiable tenet of Christian theology, an inclusive approach to interfaith dialogue can be adopted without compromising this belief. This perspective not only preserves the integrity of Christian doctrine but also offers a constructive framework for engaging with religious diversity, thereby highlighting the significance of maintaining Christ’s divinity in interfaith dialogues and its implications for Christian theology in a pluralistic society.